An array of two JPAs in a quantum two-mode squeezed radar - Milad Norouzi; Seyed Mohammad Hosseiny; Jamileh Seyed-Yazdi (Scientific Reports)
Abstract Quantum two-mode squeezed (QTMS) radar, inspired by quantum illumination but without joint measurements in the receiver, has shown promise in target detection. However, the current prototype of quantum radar, using full-microwave superconducting components, faces challenges in achieving long-range performance. In this study, we propose the integration of an array of Josephson parametric amplifiers (JPAs) in a dilution refrigerator to enhance the performance of QTMS quantum radar. Through the evaluation of signal-to-noise ratio (SNR) and receiver operating characteristic (ROC) metrics, we demonstrate the effectiveness of this enhancing strategy. Our results indicate that the presence of an array of two JPAs significantly improves both the SNR and the detection probability compared to a single JPA configuration, thereby boosting the overall performance of QTMS radar. The key factor of this improvement is the cross-correlation between JPAs, which has a notable impact on the analytical outcomes of the quantum radar. This research provides valuable insights to engineers who want to optimize the design of advanced quantum QTMS radar systems.